Let g(x) be the reflection of f(x) = 3x + 2 in the x-axis. What is a function rule for g(x)? a) g(x) = 3x – 2,
b) g(x) = –3x – 2,
c) g(x) = 3x + 2, or
d) g(x) = –3x + 2

Let g(x) be the reflection of f(x) = 3x + 2 in the x-axis. What is a function rule for g(x)? a) g(x) = 3x – 2,
b) g(x) = –3x – 2,
c) g(x) = 3x + 2, or
d) g(x) = –3x + 2

Let g(x) be the reflection of f(x) = 3x + 2 in the x-axis. What is a function rule for g(x)? a) g(x) = 3x – 2, b) g(x) = –3x – 2, c) g(x) = 3x + 2, or d) g(x) = –3x + 2

There are no comments.